Effects of Temperature and Time of Carbonization on the Properties of Bamboo (Dendrocalamus asper) Carbon - Subyakto Subyakto; Ismail Budiman; Gustan Pari (Wood Research Journal, 2012)
Lignocellulosic materials such as wood and bamboo have special characteristics when carbonized at high temperature. For example the electrical conductivity of wood and bamboo increases when carbonized at temperature of 800°C or higher. This property can be used for developing smart materials such as fiber reinforced concrete which has function as sensors for load, damage or temperature. In this experiment, betung bamboo (Dendrocalamus asper) was carbonized at different temperatures and times of carbonization. The purpose of this experiment was to observe the effect of temperature and time of carbonization on the properties of bamboo carbon. Bamboo in the form of particles were carbonized at temperature of 400°C for 300 min and continued at temperatures of 700, 800, or 900°C for 45, 60, or 90 min. Carbon properties such as yield, fixed carbon, volatile matters, and ash content were determined. Structure properties were studied by X Ray Diffraction (XRD), morphological properties were observed by Scanning Electron Microscope (SEM), and electrical conductivity was measured using LCR meter. Result shows that increasing temperature and time of carbonization have significant effects on the structure and other properties of bamboo carbon. Carbonization at temperature of 800°C for 60 min was considered as an optimum condition.